2014
DOI: 10.3174/ajnr.a4064
|View full text |Cite
|
Sign up to set email alerts
|

Parent Artery Occlusion in Large, Giant, or Fusiform Aneurysms of the Carotid Siphon: Clinical and Imaging Results

Abstract: BACKGROUND AND PURPOSE:Parent artery occlusion has long been considered the reference treatment for large/giant or fusiform aneurysms of the carotid siphon. However, meager recent data exist on this technique, which tends to be replaced by stent-assisted reconstructive techniques. In our department since 2004, we have assessed the safety, efficacy, and complication risk factors of parent artery occlusion by using coils for trapping these aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 21 publications
1
16
1
1
Order By: Relevance
“…We never encountered persistent aneurysm filling through collaterals via the ophthalmic artery. The effectiveness of our protocol of ICA balloon occlusion proximal to the aneurysm is comparable with the protocol of trapping the aneurysm with coils used by Labeyrie et al 19 However, we are in favor of our protocol because it is much easier to perform and definitely much cheaper. In addition, trapping in aneurysms located close to the ICA bifurcation is not possible because the distal ICA segment is too short to accommodate the coils.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We never encountered persistent aneurysm filling through collaterals via the ophthalmic artery. The effectiveness of our protocol of ICA balloon occlusion proximal to the aneurysm is comparable with the protocol of trapping the aneurysm with coils used by Labeyrie et al 19 However, we are in favor of our protocol because it is much easier to perform and definitely much cheaper. In addition, trapping in aneurysms located close to the ICA bifurcation is not possible because the distal ICA segment is too short to accommodate the coils.…”
Section: Discussionmentioning
confidence: 57%
“…Because long-term imaging follow-up studies after flow-diverter treatment of ICA aneurysms are not yet available, complication rates may be underestimated: delayed in-stent occlusion may go clinically undetected in the three-fourths of patients who can tolerate ICA occlusion. 30 In our opinion, supported by others, 19 the safety profile of flow diverters is not good enough to justify treatment of ICA aneurysms in patients who can tolerate carotid occlusion, especially not in patients with cavernous aneurysms that generally exhibit a benign natural history.…”
Section: Discussionmentioning
confidence: 79%
“…In a series of 56 consecutive patients receiving PAO for the treatment of large/giant aneurysms of the carotid siphon, Labeyrie et al [22] demonstrated an aneurysm retraction rate of 91% and a procedure-related permanent morbidity rate of 5%. Twenty-six percent of the patients in the Labeyrie series [22] suffered ischemic events, with symptoms resolving in most patients. Other series report ischemic stroke rates of 5-15% for PAO of ICA aneurysms with permanent occlusion rates of 90-100% [23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…While the rates of permanent aneurysm occlusion and procedure-related morbidity rates in the above series are similar to those of large and giant aneurysms in PUFS, it is important to emphasize that PAO techniques can only be used in patients who can tolerate occlusion of the carotid artery. By preserving parent artery flow, flow diverters such as the PED can be used in the treatment of patients in both the presence and absence of collateral flow [22]. …”
Section: Discussionmentioning
confidence: 99%
“…n their recent publication "Parent Artery Occlusion in Large, Giant, or Fusiform Aneurysms of the Carotid Siphon: Clinical and Imaging Results," Labeyrie et al 1 retrospectively reviewed 56 patients treated with aneurysm trapping by using detachable platinum coils. The authors make 2 controversial statements, neither of which is referenced, and with which we take issue:…”
mentioning
confidence: 99%